Complete right bundle branch block and QRS-T discordance can be the initial clue to detect S-ICD ineligibility. Issue 1 (July 2017) - Tachibana, Motomi; Nishii, Nobuhiro; Morimoto, Yoshimasa; Kawada, Satoshi; Miyoshi, Akihito; Sugiyama, Hiroyasu; Nakagawa, Koji; Watanabe, Atsuyuki; Nakamura, Kazufumi; Morita, Hiroshi; Ito, Hiroshi
Abstract: Background: In order to minimize inappropriate shocks of subcutaneous implantable cardioverter-defibrillators (S-ICD), it is important to recognize who is suitable for S-ICD indication. This study aimed to clarify what types of cardiac disease are likely to fulfill the S-ICD screening criteria and ineligible factors for S-ICD in the standard 12-lead electrocardiogram (ECG). Methods: A total of 348 patients with heart disease were enrolled. They were assessed by supine and standing ECG recording to simulate the 3 S-ICD sensing vectors and standard 12-lead ECG, simultaneously. Clinical and ECG characteristics were analyzed to compare the patients who are eligible and ineligible with S-ICD screening ECG indication. Results: The mean age of study patients was 49 ± 21 years and 244 (70%) were men. Nineteen percent of patients were unsuitable for S-ICD. There was no significant difference in ineligibility for S-ICD among cardiac diseases ( p  = 0.48). Univariate analysis showed complete right bundle branch block (CRBBB), QRS-T discordance in lead II, and QRS-T discordance in 3 leads (I, II, and aVF) were more frequent in patients who were ineligible for S-ICD than in the eligible group. Multivariate regression analysis showed CRBBB and QRS-T discordance in 3 leads were independent predictors for ineligibility of S-ICD. Conclusion: There are no differences in eligibility of S-ICD among types of cardiac diseases. CRBBB and QRS-T discordance were independent predictors for ineligibility.